Amphotericin B incorporated into egg lecithin-bile salt mixed micelles: molecular and cellular aspects relevant to therapeutic efficacy in experimental mycoses. - Brajtburg, J (1994)
The cellular activities of amphotericin B (AmB) used as Fungizone were compared with those of AmB complexed to either egg lecithin and glycocholate (Egam) or egg lecithin and deoxycholate (Edam). Under conditions in which leakage of K+ from erythrocytes and cultured L cells treated with Fungizone was almost complete, Egam and Edam containing concentrations of AmB severalfold greater than the concentration of AmB in Fungizone had no effect but retained the ability to decrease the level of retention of K+ in fungal cells. Analysis by absorption and circular dichroism spectroscopy demonstrated that when these formulations containing AmB at concentrations of less than 10(-5) M were added to buffer, the AmB dissociated slowly as monomers from Egam or Edam and dissociated rapidly as a mixture of monomers and self-associated species from Fungizone. We propose that in Egam and Edam, the absence of free AmB in the self-associated form reduces the toxicity of AmB to mammalian cells, whereas the presence of monomeric AmB results in the retention of the antifungal activities of these complexes.